Development of Spatial and Interdisciplinary Research in the Russian Regions - Wasyl Bilczak (Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The article discusses the interdisciplinary approaches to the study of regional economic systems and an integrated approach to the theory and methods of spatial development in spatial progress analysis. In addition, the administrative and the reproduction approaches of scientists to the assessment of specific territorial entities are analysed. Attention is paid to the manifestation forms of the reproduction stages with a complete cycle. Examples of specific national systems' development and political institutions are considered ed, and also the important processes directly impacting on the regionalization are highlighted. For example, economic disciplines characterize the region as spatial, socio-economic integrity, where the main processes of material production take place and the integrity of the reproduction base is preserved. The approaches of various scientific disciplines in the research on regional economic systems and specific recommendations for their development are shown.(original abstract)